Automatic Identification of Web Vulnerabilities and Risks in Web Applications - Dr. Khyati Rami, Prof. Prashant Halvadiya,Prof. Roshni Patel, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Web applications have proliferated across domains, yet their mushroomingintricacy has exacerbated susceptibility to security dangers. Standard techniques likeStatic Application Security Testing and signature-centered scanners are confined inaddressing groundbreaking and sophisticated assaults, frequently generating high false